Challenges in the Management of Spontaneous Gingival Bleeding in Patients with Hemophilia A: A Case Report - Rakanda Rizki Ramdhani Duddyarto; Anshari S. Hasibuan; Rahmat Cahyanur; Anandina Irmagita (TALENTA, 2026)
Hemophilia A, a hereditary bleeding disorder caused by factor VIII deficiency, often leads to prolonged bleeding during oral conditions and invasive dental procedures. This case report shows that poor oral hygiene and adverse oral habits can be influenced by underlying systemic conditions, showing the importance of comprehensive patient evaluation and multidisciplinary management. A 38-year-old man was referred to the Oral Medicine Clinic with complaints of painless spontaneous gingival bleeding in the left upper jaw accompanied by poor oral hygiene. The patient was not taking any routine medications at the time of presentation but underwent cryotherapy periodically since teenager, with the most recent treatment performed in 2013. Laboratory examination showed a normal platelet count, mild leukocytosis, and a prolonged activated partial thromboplastin time, showing a high risk of bleeding. The patient was prescribed chlorhexidine mouthwash by the Oral Medicine Clinic to help control plaque and gingival inflammation. Successful dental management of hemophilia A patients depends on stabilization of hemostasis, prevention of oral inflammation, and good collaboration between the dentist and hematologist before any invasive procedure is performed.